1991
DOI: 10.1021/tx00022a009
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of a chemotherapeutic agent, 6-mercaptopurine, with a direct-acting, electrophilic carcinogen, benzo[a]pyrene-7,8-diol 9,10-epoxide

Abstract: The chemotherapeutic agent 6-mercaptopurine (6-MP) has been shown to react covalently with the ultimate carcinogenic metabolite of benzo[a]pyrene, 7-r,8-t-dihydroxy-9-t,10-t-oxy-7,8,9,10-tetrahydrobenzo[a]pyrene (BPDE), in aqueous solution, forming a single adduct. NMR studies of the HPLC-purified product were consistent with its identification as 10(S)-(6'-mercaptopurinyl)-7,8,9-trihydroxy-7,8,9,10- tetrahydrobenzo[a]pyrene. Reaction kinetics were analyzed by using both HPLC separation of the products formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…characteristic of an NH group (Jeffrey et al, 1976b;Roy et al, 1991), while for H8 it is at 5.14 ppm (J = 5.4 Hz), characteristic of an OH group (MacLeod et al, 1991c;MacLeod et al, 1993). Thus, the data indicate attachment of an NH group at C7 and the presence of an OH group at C8 of BPTT.…”
Section: Resultsmentioning
confidence: 72%
“…characteristic of an NH group (Jeffrey et al, 1976b;Roy et al, 1991), while for H8 it is at 5.14 ppm (J = 5.4 Hz), characteristic of an OH group (MacLeod et al, 1991c;MacLeod et al, 1993). Thus, the data indicate attachment of an NH group at C7 and the presence of an OH group at C8 of BPTT.…”
Section: Resultsmentioning
confidence: 72%
“…Our previous data indicated that purinethiols form adducts with BPDE in vitro , in CHO cell culture, and after topical application to mouse epidermis ( ). This was correlated with decreases in DNA binding and with decreases in the biological activity of BPDE: cytotoxicity and mutagenicity in CHO cells (), and initiation of tumorigenesis in mouse skin ().…”
Section: Discussionmentioning
confidence: 99%
“…The adduct concentrations in DTP−melphalan reactions were obtained from the known starting concentrations of melphalan minus the hydrolyzed melphalan concentrations. This allowed us to determine the product ratio, f c , and the binding rate constants were obtained from double reciprocal plots according to eq 3 ( , ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations